Primary Productivity of Tanjung Balam Lake, Buluh Cina Village, Siak Hulu Sub-Regency, Kampar Regency, Riau Province Based on Oxygen Method - Rusmala Sari; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Tanjung Balam lake is an oxbow lake located beside the Kampar River and receive water from that river. A research aims to understand the primary productivity based on oxygen method and the thropic statebased on carbon concentration (gC/m3/day) was conducted in June-July 2019.  There were three sampling stations, station 1 (inlet), station 2 (middle) and station 3 (outlet). In each station there was 2 sampling points, in the surfase (15 cm) and in the water column (90 cm). Water quality parametersmeasurd were transparency, temperature, pH, dissolved oxygen, CO2 free, nitrate, phospate concentration and phytoplankton abundance. Results shown that the primary productivity was 488.8889-681.9444 gC/m3/day, transparency was 49-54 cm, temperature was 28-300C, pH was 5, dissolved oxygen was 4.03-6.56 mg/L, CO2 free was 7,92-14,59 mg/L, nitrate was 0.015-0.029 mg/L, phospate was 0.082-0.107 mg/L and phytoplankton abundance was 845,502-1,037,218 cells/L. Based on primary productivity concentration, this lake can be categorize as mesothropic condition. Keywords:Oxbow Lake, Water Quality, Phytoplankton, Mesothropic